The Spectrum of Congenital Central Nervous System Anomalies Among Stillborn: An Autopsy Based Study. Issue 3 (July 2020) - Vinutha, S. P.; Narayanappa, D.; Manjunath, G. V.; Sujatha, M. S.; Sapna Patel, M. C.; Bhat, Deepa
Background: Congenital central nervous system (CNS) anomalies are the structural or functional abnormalities of the brain and spinal cord that occur during the intrauterine developmental process. Purpose: The present study aims to detect the prevalence of congenital CNS anomalies among stillborn fetuses, the association between congenital anomalies and maternal factors, and also the association between autopsy and ultrasound findings. Methods: This study was conducted on 50 stillborn fetuses, obtained from the Department of Obstetrics and Gynecology at JSS Medical College and Hospital, Mysuru. The fetuses were fixed in 10% formalin and autopsies were performed as per the standard fetal autopsy protocol. The congenital CNS anomalies were studied in detail. Results: CNS anomalies were the most common congenital anomalies observed. Out of the total 50 stillborn fetuses studied, CNS anomalies were found in 17 fetuses and their occurrence was more common among male stillborn than females. Meningomyelocele was the most common anomaly, followed by anencephaly. The other anomalies documented were meningocele, encephalocele, meningoencephalocele, agenesis of the corpus callosum, craniorachischisis, bifid cerebellum with hypoplastic vermis, holoprosencephaly, and sirenomelia. Fisher's exact test showed a significant association between maternal hypothyroidism and congenital CNS anomalies ( P < .05). The autopsy confirmed the ultrasound findings in 40 (80%) fetuses. There were significant additional findings observed in seven (14%) fetal autopsies and ultrasound diagnosis completely changed in three (6%) cases, after the final autopsy procedure. Conclusion: The fetal autopsy is the single most directly evident investigation, which gives information that changes or significantly improves the clinical diagnosis. A multidisciplinary holistic approach toward pregnancy will help to detect any kind of abnormality in the fetus and thus to take a timely decision toward the management.